Enabling symptom self-management via use of an electronic patient-reported outcomes (ePRO) system to increase self-efficacy of patients with cancer receiving active chemotherapy treatment - Grigorios Kotronoulas; Eileen Furlong; Jo Armes; Christine Miaskowski; Elisabeth Patiraki; Kathi Apostolidis (Frontiers in Public Health, 2015)
Background: In recent years, the shift in cancer services from traditional tertiary care to care delivered within communities has increased the need for patients to engage in self-care activities in order to prevent or reduce the severity of numerous and complex-side effects (McCorkle et al., 2011) and make important health decisions when at home in the absence of clinicians (Butow et al., 2012). The actual degree of engagement in self-management may be dependent on patients’ perceived competence or self-efficacy to perform such activities (Fenlon et al., 2015). Self-efficacy has been defined as “a person’s belief to execute courses of action required to deal with a prospective situation” (Bandura, 1977, 2001). One’s beliefs in their capability to successfully manage tasks and consequently influence situations that impact their lives constitutes a central part of human agency, and can be influenced by performance accomplishments (Bandura, 1989, 2001). Whilst self-efficacy can enable engagement in self-management, actual participation in self-management activities can further increase one’s perceived ability to undertake such activities; it is thus obvious that a bi-directional association between self-management and self-efficacy exists. Supporting a shift in clinical practice with innovative technological systems affords a solution to the increasing demands placed on acute care by enabling the delivery of care in the home and community setting (Basch et al., 2011; Carpenter et al., 2008). Such remote monitoring systems facilitate the provision of clear lines of real-time communication between patients and their health care providers (Basch et al., 2011), and can deliver organised self-management advice tailored to the individual’s clinical characteristics and severity/distress of symptoms of anti-cancer treatment.